Livros didáticos de língua portuguesa e representações de leitura a partir de suportes midiáticos - Barbosa, Raquel Lazzari Leite [UNESP] (2011)
Didactic texts compose communication and representation systems. By them societies communicate with their children, their youth, transmit them live representations, symbols, ways of understanding speeches and delimit their study fields. This article presents a discussion about the medias used by Portuguese language text books selected by the Ministry of Education Textbook National Program (PNDL – in Portuguese), in order to observe the foundation of actions, movements and media insertion at school. The analysis allows us to see the consolidation of an individualist profile among the strategies of using medias at school, among others aspects.